2014
DOI: 10.1007/s00018-014-1591-6
|View full text |Cite
|
Sign up to set email alerts
|

The amino terminus extension in the long dipeptidyl peptidase 9 isoform contains a nuclear localization signal targeting the active peptidase to the nucleus

Abstract: was previously considered as a purely cytosolic peptidase, localizes to the nucleus and is active there, raising the intriguing possibility that the longer DPP9 isoform may regulate the activity or stability of nuclear proteins, such as transcription factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…S1A) with minimal cross‐contamination, verifying the fractionation technique. In line with previous publications , DPP9 was readily detectable in each fraction (Fig. S1A).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…S1A) with minimal cross‐contamination, verifying the fractionation technique. In line with previous publications , DPP9 was readily detectable in each fraction (Fig. S1A).…”
Section: Resultssupporting
confidence: 92%
“…Recent work demonstrated that alternately translated DPP9 isoforms are localized to different subcellular compartments , necessitating analyses on three separate cell lysate fractions enriched for cytoplasmic, membrane or nuclear proteins. In addition to the cytosolic proteome, about 16% of all DPP9 substrates identified in our study were annotated with nuclear localizations in the UniProt database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In healthy conditions, the proteases are readily inactivated by the abundant presence of endogenous inhibitors in the cytosol. In cancer cells with reduced expression levels of the inhibitors, however, the proteases remain active and eventually cause severe damage, ultimately leading to cell death cysteine cathepsins and legumain have also been reported in unusual cellular compartments (Justa-Schuch et al 2014;Lee et al 2011;Melo et al 2014).…”
Section: Endo-lysosomal Cysteine Peptidases: Myths and Common Questionsmentioning
confidence: 99%
“…However, localisation of DPP9 on the surface of immune cells was also reported. In addition, the long form of DPP9 was shown to localise to the nucleus . Redistribution of intracellular DPP9 towards the ruffling membrane upon cell stimulation with phorbol 12‐myristate 13‐acetate or epidermal growth factor has also recently been shown …”
Section: Introductionmentioning
confidence: 87%